16
$\begingroup$

Prove that :

$$2\left(\frac{1}{2}\right)^{\phi/2}+2< \pi$$ where $\phi:=\frac12(1+\sqrt{5})=1.618\ldots$ is the golden ratio.

How I came across this approximation?

Well, I was studying the following function:

$$f(x)=x^{\phi(1-x)}+(1-x)^{\phi x }+2$$

The approximation corresponds to the maximum of $f(x)$

I can solve it using power series it's not hard and using some approximation of $\pi$

But I would like to know if there is a proof without derivatives using by example inequality like Bernoulli's inequality .

Can you help me ?

Thanks a lot for all your contributions.

$\endgroup$
3
  • 1
    $\begingroup$ You need to go up to $72/89$ with the Fibonacci-based lower bounds to $\phi/2$ to make that estimate work. Curious :-) $\endgroup$ – Jyrki Lahtonen Jun 27 '20 at 7:45
  • $\begingroup$ Nice function. What approximation of pi did you use and what did you expand in power series ? Could you write some more details about your derivation ? $\endgroup$ – Thomas Jun 27 '20 at 8:35
  • 1
    $\begingroup$ Equivalently the fixed point of $f(x)=1-2^{-\cos(2x/5)}$ is less than $\pi/2$. $\endgroup$ – TheSimpliFire Jun 27 '20 at 10:24
2
+50
$\begingroup$

If we'll prove that $$2^{\sqrt5}>\frac{212}{45},$$ so it's enough to prove that: $$\frac{2}{\sqrt[4]2\cdot\sqrt[4]{\frac{212}{45}}}+2<\pi$$ or $$\sqrt[4]{\frac{90}{53}}<\pi-2$$ for which it's enough to prove that $$\sqrt[4]{\frac{90}{53}}<\frac{1613}{1413},$$ which is true because $$1413^4\cdot90-1613^4\cdot53=-1802797643<0.$$ I hope it will help.

$\endgroup$
1
$\begingroup$

To prove the main result

$$2\left(\frac{1}{2}\right)^{\frac{\phi}{2}}+2<\pi$$

we shall show that $ \pi <\sqrt{10}$ and interestingly, we also deduce that $ 3<\pi<4$

Preliminaries

Consider the set $$S=\left\{X_n= \frac{1}{n^3(n+1)^3} : n\in\mathbb {N} \right\}$$ and here we show that set $S$ is bounded set with lower and bounds $0$ and $\frac{1}{8}$ respectively. Note that for $n\geq 1$ the $$ \begin{aligned} S_{n+1}-S_n & =\frac{1}{(n+1)^3}\left[\frac{1}{(n+2)^3}-\frac{1}{n^3}\right]\\ & =\frac{1}{(n+1)^3}\left[\frac{n^3-(n+2)^3}{n^3(n+2)^2}\right]\cdots(1)\end{aligned}$$ since for all $n>1$, $ n< n+2\implies n^3-(n+2)^3<0$ from $(1)$ it follows that $ S_{n+1}-S_n <0$ implies the sequence $X_n$ contained in set $S$ is a decreasing sequence and thus $$ \begin{aligned} \operatorname{sup}\left\{X_n : n\in \mathbb{N}\right\}&=\frac{1}{8}<1\\ \operatorname {inf}\left\{X_n:n\in\mathbb{N} \right\}&=0\end{aligned}$$Therefore, $ 0 < X_n \leq \frac{1}{8} <1$. Futher, $n^3(n+1)^3> n(n+1)=Y_n$ and hence $$0 <\sum_{n\geq 1} X_n < \sum_{n\geq 1} (Y_n)^{-1}=1\cdots(2)$$ since we have telescoping series as $\displaystyle \sum_{n\geq 1} (Y_n)^{-1} =\sum_{n\geq 1} \left(\frac{1}{n}-\frac{1}{n+1}\right)=1$ Now $$\begin{aligned} \sum_{n\geq 1} X_n & =\sum_{n\geq 1} \left(\frac{1}{Y_n}\right)^3\\&=\sum_{n \geq 1}\left(\frac{1}{n^3}-\frac{1}{(n+1)^3}\right)\\&-\sum_{n\geq 1}\frac{3}{(Y_n)^2}=\zeta(3)-\zeta(3)+1\\& 1-3\sum_{n\geq 1} \left(\frac{1}{n^2}+\frac{1}{(n+1)^2}\right)\\&-2\sum_{n\geq 1}\frac{1}{(Y_n)}= 1-6\zeta(2)+9 \\&= 10-\pi^2\end{aligned}$$ and thus from $(2)$ $$\sum_{n\geq 1}X_n >0\implies \pi <\sqrt{10}$$ since $ 9-\pi^2 < 10-\pi^2<16-\pi^2$ which implies $3< \pi < 4$.

Proof of the main result

If the left hand expression of main result has to be less than $\pi$ then it should also be less than $\sqrt {10}$. To prove the result we suppose that the inequality is true. That is; $$A= 2\left(\frac{1}{2}\right)^{\frac{\phi}{2}}+2 < \pi ,\;\; A< \sqrt {10}$$ Squaring both sides we yield $$\begin{aligned}\left( \frac{1}{2}\right)^{\phi}+ \left(2\left(\frac{1}{2}\right)^{\frac{\phi}{2}}+2\right)-1<\frac{5}{2}\end{aligned}\\ \left(\frac{1}{2}\right)^{\phi}+A<\frac{7}{2}$$ hence$$\left(\frac{1}{2}\right)^{\phi} <\frac{7-2\sqrt{10}}{2}=\left(1+\frac{5-2\sqrt{10}}{2}\right)^{\frac{1}{\phi}}=(1+y)^{\phi^{-1}}$$ since $ \phi>1\implies \frac{1}{\phi}<1$ and hence by Bernoulli inequality we have $$(1+y)^{\phi^{-1}}<1+ \frac{y}{\phi}=\\ 1-\frac{15}{(5+2\sqrt{10})(1+\sqrt{5})}<1-\frac{15}{11 \cdot 3} =1-\frac{15}{33}=\frac{18}{33}$$ Since $$\begin{aligned} \frac{7-2\sqrt {10}}{2}=(1+y)^{\phi{-1}} <\frac{18}{33}\end{aligned}$$. We claim that $A<\sqrt {10}$ which also says $\frac{1}{2} <(1+y)^{\phi^{-1}}$ also we have $(1+y)^{\phi^{-1}} <\frac{18}{33}$. Therefore we must have $\frac{1}{2} < \frac{18}{33}$ which is true since $$\frac{1}{2} -\frac{18}{33} =\frac{33-36}{66} =-\frac{1}{22}<0$$ As we claimed inequality to be true and hence we came up $-\frac{1}{22}<0$ to be true and thus,

$$2 \left(\frac{1}{2}\right)^{\frac{\phi}{2}}+2<\pi$$ must be true.

$\endgroup$
3
  • 2
    $\begingroup$ Assuming the details are correct and you have proved $A < \sqrt{10},$ how does it follow that $A < \pi$? $\endgroup$ – Calum Gilhooley Jul 2 '20 at 12:12
  • $\begingroup$ @Calum Gilhooley, Can you please check once again, I had made few changes in the solution? $\endgroup$ – Naren Jul 3 '20 at 18:37
  • $\begingroup$ (I'm sorry about the slow response. I was unable to post for 7 days. It's a long story!) Putting the details of your argument in brackets, for the moment, its overall structure appears to be: if $A < \pi,$ then $A < \sqrt{10},$ and this is true (assuming that the aforementioned details are correct, and also using the proposition $\pi < \sqrt{10},$ which is correct in any case), therefore the hypothesis $A < \pi$ is true. But this is a fallacious argument. (I haven't downvoted it yet, in case I have misunderstood what you're getting at.) $\endgroup$ – Calum Gilhooley Jul 10 '20 at 15:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.